Information needs and information practices of agricultural scientists in Sri Lanka - Mudannayake, Irangani (1987)
The study aims to describe the information needs and information seeking behavior of agricultural scientists in Sri Lanka with a view to provide baseline information for the agricultural libraries to make user profiles of their clientele and to improve agricultural information dissemination in the country.